The nuclear receptor REV‐ERBα represses the transcription of growth/differentiation factor 10 and 15 genes in rat endometrium stromal cells. Issue 2 (26th January 2016) - Zhao, Lijia; Isayama, Keishiro; Chen, Huatao; Yamauchi, Nobuhiko; Shigeyoshi, Yasufumi; Hashimoto, Seiichi; Hattori, Masa‐aki
Abstract: Cellular oscillators in the uterus play critical roles in the gestation processes of mammals through entraining of the clock proteins to numerous downstream genes, including growth/differentiation factor ( Gdf ) 10 and Gdf15 . The expression of Gdf10 and Gdf15 is significantly increased in the uterus during decidualization, but the mechanism underlying the regulation of Gdf gene expression in the uterus is poorly understood. Here, we focused on the function of the cellular oscillators in the expression of Gdf family by using uterine endometrial stromal cells (UESCs) isolated from pregnant Per2‐dLuc transgenic rats. A significant decline of Per2‐dLuc bioluminescence activity was induced in in vitro decidualized UESCs, and concomitantly the expression of canonical clock genes was downregulated. Conversely, the expression of Gdf10 and Gdf15 of the Gdf was upregulated. In UESCs transfected with Bmal1‐ specific siRNA, in which Rev‐erbα expression was downregulated, Gdf10 and Gdf15 were upregulated. However, Gdf5, Gdf7, and Gdf11 were not significantly affected by Bmal1 silencing. The expression of Gdf10 and Gdf15 was enhanced after treatment with a REV‐ERB α antagonist in the presence or absence of progesterone. Chromatin immunoprecipitation‐PCR analysis revealed the inhibitory effect of REV‐ERB α on the expression of Gdf10 and Gdf15 in UESCs by recognizing their gene promoters. Collectively, our findings indicate that the attenuation of REV‐ERB α leads to an upregulation of Gdf10 and Gdf15 in decidual cells, in which cellular oscillators are impaired. Our results provide novel evidence regarding the functions of cellular oscillators regulating the expression of downstream genes during the differentiation of UESCs. Abstract : The attenuation of REV‐ERB α leads to an up‐regulation of Gdf10 and Gdf15 in decidual cells, in which cellular oscillators are impaired. Our results provide novel evidence regarding the functions of cellular oscillators regulating the expression of downstream genes during the differentiation of UESCs.